Criminal Act To Transfer, Duplicate, Or Rent Out Objects What Is The Object Of Fiduciary Guarantee (Study of Decision Number 549/Pid.Sus/2023/PN Tjk) - Zulfi Diane Zaini; Renard Raja Abdullah (International Journal of Education, Vocational and Social Science, 2026)
The practice of securing movable property can constitute a criminal act if someone intentionally embeds, transfers, or pledges a fiduciary guarantee object. Verdict Number 549/Pid.Sus/2023/PN Tjk confirms that this act occurred in July 2021 at PT BFI Finance Lampung, Metro branch, under the jurisdiction of the Sukadana District Court. Since most witnesses were in Bandar Lampung, the defendant was detained at the Lampung Police Detention Center in accordance with Article 84 paragraph (2) of the Criminal Procedure Code. The research questions in this study are how criminal sanctions are imposed on perpetrators of the transfer, duplication, or leasing of fiduciary guarantee objects, and how the judge's considerations are based on legal facts in the verdict. The research method uses both normative and empirical juridical approaches, employing primary and secondary data collected through library research and field research, and analyzed qualitatively from a juridical perspective. The results indicate that the defendant, Made Susilo, was proven guilty of transferring a fiduciary guarantee object without the written consent of the fiduciary recipient, in accordance with Article 23 paragraph (2) of Law No. 42 of 1999 on Fiduciary Security. Based on the second alternative charge by the Public Prosecutor, the defendant was sentenced to 3 months in prison and a fine of IDR 1,000,000, which, if unpaid, would be converted to 1 month of imprisonment. The judge's considerations consider the existence of a valid fiduciary agreement and the defendant's intentional actions, including that the act violated positive law and the principle of good faith, reflecting prudence and proportionality in upholding justice. The study recommends that financing companies regularly monitor fiduciary objects and include clear legal protection clauses in agreements. Law enforcement officers are advised to be more proactive, and the public should understand the legal consequences of transferring or leasing fiduciary objects without authorization to prevent violations and potential losses.